A case study for designing and testing a tailings storage facility cover - Haagner, ASH; van Wyk, SJ (Mine Closure 2022: 15th International Conference on Mine Closure, 2022)
Due to the extreme and volatile geochemical properties of gold tailings, most tailings storage facilities (TSFs) will need to be clad, capped or covered for final rehabilitation to be effective in the long-term. Without such interventions, groundwater and soil contamination are almost inevitable, and mine closure (with associated liability relinquishment) an impossibility. We undertook a series of geochemical, pedological and hydraulic tests on potential cover soils for a large (>650 Ha) gold TSF in South Africa. The tests included detailed work on the variability of the tailings material as well. The tailings proved to be acidic and saline, with high concentrations of total and leachable heavy metals. The testing showed that the tailings was net acid generating, with high sulphur content and very low neutralisation potential. Kinetic testing provided unacceptably poor leachate qualities. Hydraulically, the tailings material proved to have ideal store-and-release properties. The range of soils present were also tested and found to have insufficient neutralising potential to combat the acid production from the tailings, but the hydraulic properties appeared promising to support phyto-evaporation. Adequate soil volumes were located and mapped. The data were used to inform potential cover designs, which were the product of erosion modelling, unsaturated flow modelling, geochemical modelling and geohydrological risk modelling. The model outputs suggested a series of potential phyto-evaporative transpiration (PET) covers that could be suitable to achieve the closure objectives of <5% of mean annual rainfall percolating through the cover and into the underlying tailings and through the foundation of the TSF. We then built a series of four lysimeters (with a control site), each representing a different potential PET cover configuration. The total cover thicknesses varied from 450 mm to 800 mm. In each, we measured vegetation dynamics (plant density, leaf area, contact cover, species composition), soil moisture depletion and volume, run-off, seepage, and sediment movement. Most of these parameters were measured hourly, via in situ probes, whilst other measurements were recorded monthly during the summer growth season and every second month during the winter. Measurements continued for five years (2017–2021). The data collected from the lysimeters validates the model predictions and shows that the model outputs are conservative, with lower seepage rates being reported for all trial covers. The thickest and thinnest soil covers yielded relatively poor performance, with the addition of rock not benefitting any of the performance criteria. Ultimately, the characterisation, modelling and testing of potential covers have allowed us to identify the most appropriate long-term closure cover of the gold TSF and has resulted in a cost saving of ZAR 200 million over the initial cover cost estimates. If the designed cover is implemented correctly, the active post-closure water management costs are substantially lowered, and the contamination plume will start to recede within 25 years of decommissioning.
Keywords: tailings closure; phyto-evaporative cover; lysimeter monitoring